The Effect of Core Values Akhlak Effectiveness on Employee Performance at Indonesian Sharia Bank in Bandung City - Rini Lestari; Nurfahmiyati Nurfahmiyati; Magnaz Lestira Oktoroza (Kajian Akuntansi, 2022)
This research is motivated by the many problems that occur in Indonesian Islamic Banks related to the decline in banking performance caused by the many cases of embezzlement of customer funds and the provision of fictitious financing so that it indicates the low effectiveness of implementing the core value of AKHLAK which results in poor banking performance which is nothing but a reflection of poor performance. employee. The purpose of this study was to examine the effect of the effectiveness of the core value of AKHLAK on employee performance. The research was conducted at the Indonesian Sharia Bank (BSI) in the city of Bandung, with the method used was a verification method with a quantitative approach. The distribution of questionnaires was carried out as a data collection technique with respondents from all BSI employees in the city of Bandung.